2006
DOI: 10.1007/s11357-006-9021-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary differences between centenarians residing in communities and in skilled nursing facilities: the Georgia Centenarian Study

Abstract: The purpose of this study was to examine the dietary habits among centenarians residing in community settings (n=105) and in skilled nursing facilities (n=139). The sample was a population-based multi-ethnic sample of adults aged 98 years and older (N=244) from northern Georgia in the US. Compared to centenarians in skilled nursing facilities, those residing in the community were more than twice as likely to be able to eat without help and to receive most of their nourishment from typical foods, but they had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
(13 reference statements)
1
15
0
Order By: Relevance
“…However, in this study we found that compared to centenarians residing in the community, centenarians in skilled nursing facilities had a superior dietary patterns with higher dairy food intake (41) and they were more likely to take a vitamin D-containing supplement (32.8% vs. 54.1%, unadjusted, p < 0.01). Thus, residence in a nursing home is not necessarily a strong risk factor for vitamin D insufficiency when dairy foods (e.g., vitamin D-fortified as indicated milk) and vitamin D-containing supplements are provided.…”
Section: Discussionmentioning
confidence: 50%
“…However, in this study we found that compared to centenarians residing in the community, centenarians in skilled nursing facilities had a superior dietary patterns with higher dairy food intake (41) and they were more likely to take a vitamin D-containing supplement (32.8% vs. 54.1%, unadjusted, p < 0.01). Thus, residence in a nursing home is not necessarily a strong risk factor for vitamin D insufficiency when dairy foods (e.g., vitamin D-fortified as indicated milk) and vitamin D-containing supplements are provided.…”
Section: Discussionmentioning
confidence: 50%
“…Participants who had missing data for supplement use were categorized as not receiving supplements. Questions regarding food intake were adapted from the Mini-Nutritional Assessment (30,31) and the response categories represented current frequency of consumption of food groups, including dairy products (milk, yogurt, and cheese); meat, fish, or poultry; orange/yellow vegetables; green vegetables; and citrus and non-citrus fruit and juice. The total food score, ranging from 0 to 5, was based on comparisons with the Dietary Guidelines for Americans (32) 1,600-calorie meal pattern for sedentary older adults, as previously described (31).…”
Section: Methodsmentioning
confidence: 99%
“…Rather, most studies have focused on individuals who are community-dwelling, autonomous and almost exclusively on those who are cognitively intact (e.g., Chou & Chi, 2002;Hsu, 2010;Willcox, Willcox, Shimajiri, Kurechi, & Suzuki, 2007). Studies that distinguished between dwelling differences among participants have generally noted higher levels of impairment in multiple areas of functioning among the institutionalized relative to their community-dwelling peers with little emphasis placed on subjective financial perceptions (Johnson, Davey, Hausman, Park, & Poon, 2006). Nevertheless, Randall et al (2010) found that centenarians living in nursing homes self-reported significantly lower social resources than centenarians living in either private homes or personal care facilities and concluded that residential setting was associated with social resource adequacy.…”
Section: Economic Perceptions and Institutional Statusmentioning
confidence: 99%
“…Noninstitutionalized respondents who reported not having resources to meet future needs had mean depression scale scores that were more than double of those who reported being able to meet future needs. While no study of centenarians that we know of has examined differences in economic perceptions by dwelling status, this study adds to the work of others who have examined other outcomes (e.g., Johnson et al, 2006) regarding dietary differences or Randall, Martin, MacDonald, and Poon (2010) regarding social resources) in this way.…”
mentioning
confidence: 93%